Eulogy - Haft, Steven; Lewis, Richard B.; D'Amico, Kirk; Clancy, Michael; Azaria, Hank 1964- .; Bradford, Jesse 1979- .; Deschanel, Zooey 1980- .; SouthPaw Entertainment; S.R.O. Entertainment; Equity Pictures Medeinfonds GmbH & Co. KG. (Sta. Monica, California Lions Gate Home Entertainment, 2004)
When three generations of a deliciously dysfunctional family gather to bury the family patriarch, the beloved grand daughter of the deceased is given the task of delivering the eulogy. In the days leading up to the funeral, family secrets are revealed, old grudges resurface and the household erupts with renewed vigor.
Casting by Nancy Nayor ; Music Supervisor, Chris Violette ; Music by George S. Clinton ; Editor, Richard Halsey ; Production designer, Dina Lipton ; Director of photography, Michael Chapman ; Co-producers, Stefan Jonas, Jeanne Van Cott ; Executive producers, Rory Rosegarten, Jonas McCord, Shelly Glasser, Lucas Foster, Kendal Morgan, Bo Hyde.
Hank Azaria, Jesse Bradford, Zooey Deschanel, Glenne Headly, Famke Janssen, Piper Laurie, Kelly Preston, Ray Romano, Rip Torn, Debra Winger.
DVD (Region 1, NTSC) ; Widescreen (16:9) ; 5.1 Dolby Digital Surround, 2.0 Dolby Digital.
In English with Spanish subtitle.
Keywords: Family -- Drama; Funeral rites and ceremonies -- Drama; Feature films; Comedy Film